Поширення раритетних видів родини Betulaceae S.F.GRAY у Волинській області (Україна) - Кузьмішина, Ірина Іванівна; Коцун, Лариса Олександрівна; Войтюк, Василь Петрович; Лісовська, Тетяна Павлівна; Баранський, Олександр Ростиславович; Kuzmishyna, Iryna I.; Kotsun, Larysa O.; Voitiuk, Vasyl P.; Lisovska, Tetiana P.; Baranskyi, Oleksandr R. (Національний науково-природничий музей НАН України, 2014)
The article reports own field research materials and the results of the literature review from the territory of Volyn region about the dissemination of plant species from family Betulaceae (Betula humilis Schrank, B. obscura A.Kotula, Alnus incana (L.) Moench.), which are staying under the protection of the Red Book of Ukraine and regionally rare. Brief descriptions, localities and data on distribution are given.
The dissemination of rare species of the family Betulaceae S.F.GRAY in the Volyn region
Keywords: родина Betulaceae S.F.Gray; Волинська область; Червона книга України; рідкісні види рослин; охорона; Red Book of Ukraine; rare species of plants; Volyn region; protection